2010
DOI: 10.2527/jas.2009-2677
|View full text |Cite
|
Sign up to set email alerts
|

Ileal digestibility of amino acids in conventional, fermented, and enzyme-treated soybean meal and in soy protein isolate, fish meal, and casein fed to weanling pigs1

Abstract: An experiment was conducted to determine the apparent (AID) and standardized (SID) ileal digestibility of CP and AA in weanling pigs of 4 soybean products, fish meal, and casein. The 4 soybean products were conventional dehulled soybean meal (SBM), soy protein isolate (SPI), fermented soybean meal (FSBM), and enzyme-treated soybean meal (ESBM). Seven weanling barrows (initial BW: 10.9 +/- 2.3 kg) were individually fitted with a T-cannula in the distal ileum. The barrows were allotted to a 7 x 7 Latin square de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
89
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 35 publications
(44 reference statements)
32
89
6
Order By: Relevance
“…The concentrations of CP and AA in SPC and FSBM were also similar to the results from Urbaityte et al (2009) and Cervantes-Pahm and Stein (2010). In current study, SPC and FSBM contained more CP, AA, Ca, P and less glycinin, β-conglycinin and TI than that of SBM, the finding was consistent with the results of Chen et al (2010), who found that FSBM and SPC contained higher protein, most of essential AA, and lower soybean antigen proteins than untreated raw SBM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The concentrations of CP and AA in SPC and FSBM were also similar to the results from Urbaityte et al (2009) and Cervantes-Pahm and Stein (2010). In current study, SPC and FSBM contained more CP, AA, Ca, P and less glycinin, β-conglycinin and TI than that of SBM, the finding was consistent with the results of Chen et al (2010), who found that FSBM and SPC contained higher protein, most of essential AA, and lower soybean antigen proteins than untreated raw SBM.…”
Section: Discussionsupporting
confidence: 90%
“…Diet 1 was a nitrogen-free diet which was used to determine endogenous AA losses. The three experimental diets were formulated with regard to previous research which observed that inclusion of increased amounts of SBM in diets fed to weaning pigs may cause allergic reactions, which potentially could influence the results for the diet containing SBM (Cervantes-Pahm and Stein, 2010). In the present study, diets 2, 3 and 4 were formulated to contain different levels of each soybean product to provide the same amount of CP (12.88%) in each diet.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are inconsistent with previous data (Zamora and Veum 1988;Feng et al 2007;Yoo et al 2009) which may be due to differing particle sizes and KOH solubility (Parsons et al 1991). The crude protein and amino acids composition of ETSM are similar to the values reported by Zhu et al (1998) and Cervantes-Pahm and Stein (2010).The concentration of lysine calculated as a percentage of crude A possible reason for this observation may be that these meals were heat-damaged during drying; heat damage may result in Maillard reactions that will destroy some of the lysine in the products (Stein et al 2009). …”
Section: Discussioncontrasting
confidence: 99%
“…The values for the AID of amino acids in FSMB, FSMC and ETSM diets that were measured in this experiment were also greater than for conventional SBM. We observed that the overall SID of crude protein of SBM, FSMA, ETSM and FSMC was 84.32, 81.13, 88.87 and 89.25%, respectively, which was similar to the study conducted by Cervantes-Pahm and Stein (2010). High protein digestibility ensures that the protein's content of essential amino acids is readily bioavailable (Urbaityte et al 2009).…”
Section: Discussionsupporting
confidence: 77%
“…This is contrary to the current study, where protein level had no effect on potential proteolytic Enterobacteriaceae at the ileal level, and there was even a negative linear effect on the Bacteroides group in ileal digesta of piglets fed the SBM-based diets. However, at the fecal level, higher contents of CP in the diet stimulated growth of Bacteroides group in piglets fed the SBM-based diets but not in the casein-based diets, maybe due to the higher availability of less digestible protein from SBM compared to casein [37]. Accordingly, Heo et al [38] determined higher concentrations of fecal ammonia in weaned piglets fed a high protein SBM-based diet (243 g CP/kg) compared to a low protein SBM-based diet (173 g CP/kg), together with a higher incidence of diarrhea, measured as fecal score, probably due to an increased protein fermentation.…”
Section: Discussionmentioning
confidence: 83%